Florianópolis: an evolutionary analysis of the innovative development of the city from their innovation ecosystem (Revista Brasileira de Contabilidade e Gestão, 2017)
This study sought to carry out an evolutionary analysis of Florianópolis in terms of its ecosystem of innovation, its scope and actions. This innovative ecosystem had as its starting point the creation of the Federal University of Santa Catarina in 1960. And today human capital stands out with the presence of several undergraduate and postgraduate courses. In addition, two parks are among the top in Brazil. It is also worth mentioning the presence of the two main and best Brazilian incubators, two pre- incubators, two FabLabs and three accelerators. In general, there are several institutions that support innovation and entrepreneurship in the capital.
Keywords: innovation; entrepreneurship; city; Florianópolis; innovation ecosystem